Deja review. - Chen, Eric M.; Chen, Joseph 1993- (Deja review, 2020)
"This high-yield, rapid-fire Q&A book simulates flashcards in a book to help medical students review microbiology and immunology for their course exams as well as prepare for the USMLE Step 1. It is also a great review for students in basic courses in other health-related programs"-- Provided by publisher.